The heartless one - Hamm, Emma (Gravesinger Series, 2026)
She won the heart of Death...now she must fight for the hearts of her people. Jessamine never expected to be on the Deathless One's side--let alone be in love with him. But now that Elric has returned to his corporeal form and Jessamine has joined the coven of witches that sustain his power, the two are stronger than ever. But the kingdom is still in turmoil. Jessamine and Elric must prepare their coven of witches to meet the kingdom's forces in battle--before the man who's usurped her throne learns how to harness the power of Elric's fellow gods. How can Jessamine accept that to fight for her kingdom, she might have to fight against it? --